The Effect of Service Quality on Customer Satisfaction at Mie Celor 26 Ilir H.M Syafei Z Palembang - Mifthahul Maula; Esya Alhadi (Department of Business Administration Politeknik Negeri Sriwijaya, 2022)
This study aims to determine the effect of service quality on consumer satisfaction at Mie Celor 26 Ilir H.M Syafei Z Palembang. The methodology used in this research is descriptive quantitative. The accidental sampling technique was applied. The participants were consumers at the stall by a total of 100 respondents. Based on the t-test, the value of t-count was higher than t-table (3.860 > 1.984). It means that service quality has a significant effect on consumer satisfaction. While in the calculation of the coefficient of determination, the result obtained was 55%. Cornbach's Alpha value on service quality also showed that it was higher than the crisis value, which was 0.902, and then the variable was declared reliable since exceeded 0.600.